1987
DOI: 10.1002/bip.360260813
|View full text |Cite
|
Sign up to set email alerts
|

Conformational behavior of the polysaccharide backbone of murein

Abstract: SynopsisThe energetically possible conformations for the alternating heteropolysaccharide backbone of murein, consisting of N-acetylglucosamine and N-acetylmuramic acid, were calculated using an empirical approach. The calculations were carried out for regular as well as for random-chain polymers, resulting in a model for the saccharide strands featuring extended chains with a length increment of 0.98-1.02 nm per disaccharide unit and peptide attachment sites at every second saccharide residuum pointing into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Peptidoglycan strands have a natural right-handed twist (15,30), nascent (17) and whole material (Fig. 2 C and D) is arranged helically, and cells of B. subtilis can grow helically under some conditions (18).…”
Section: Discussionmentioning
confidence: 99%
“…Peptidoglycan strands have a natural right-handed twist (15,30), nascent (17) and whole material (Fig. 2 C and D) is arranged helically, and cells of B. subtilis can grow helically under some conditions (18).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the presence of the rather bulky lactyl group at MurNAc allows less rotation. About four disaccharide units (eight sugar residues) are required for one turn, and consequently, the peptides protrude from the glycans in a helical pattern (3,50,55) (Fig. 1B).…”
Section: Structural Modelsmentioning
confidence: 99%
“…This pentapeptide stem participates in an interglycan cross-linking reaction, thus creating the cell wall polymer. In contrast to the two other ␤-1,4-linked glycan biopolymers, cellulose (repeating glucose) (1)(2)(3)(4) and chitin (repeating NAG) (5-7) for which the 3D structure is solved, the structure of the bacterial cell wall has remained elusive because of its complexity and the lack of pure and discrete segments for structural study (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Herein we describe the 3D structure, determined in aqueous solution by NMR, of a 2-kDa synthetic NAG-NAM(pentapeptide)-NAG-NAM(pentapeptide) tetrasaccharide cell wall segment.…”
mentioning
confidence: 99%
“…Because of the critical significance of the cell wall to bacterial survival, and the exploitation of the cell wall biosynthetic enzymes for the chemotherapeutic intervention of infections, many experimental and theoretical studies have addressed the cell wall structure. Despite diffraction studies carried out Ͼ30 years ago on cell wall extracted from bacteria, which strongly suggested that the peptidoglycan polymer possessed regular order (11), the 3D structure of the cell wall is not known. An excellent account of the historical development of the hypotheses for the cell wall structure is given by Dmitriev, Toukach, and Ehlers in their recent review (18).…”
mentioning
confidence: 99%